Two Behavioral Models of the Electronically Controlled Generalized Current Conveyor of the Second Generation - Jerabek, Jan; Sotner, Roman; Kartci, Aslihan; Herencsar, Norbert; Dostal, Tomas; Vrba, Kamil (IEEE, 2015)
This contribution presents two behavioral models of voltage-controlled generalized current conveyors of the second generation based on the commercially available devices. The prepared models are suitable for the practical experiments, before expensive fabrication of transistor-level implementation of whole active device is performed. Both models offer three standard terminals (X - current input terminal, Y - voltage input terminal, Z - current output terminal) and have a possibility of electronic control of its generally defined parameters (current transfer/gain B in direction X -> Z, voltage gain A in direction Y -> X, generally non-zero resistance R-X of current input terminal X). Functionality of the presented behavioral models was verified just by PSpice simulations in this preliminary stage.
Keywords: Electronic control; current gain; generalized current conveyor of second generation; intrinsic resistance control; voltage gain; GAIN; Engineering; Telecommunications